(untitled) (TAJ: Journal of Teachers Association, 2009)
Metronidazole infusion had been prepared and studied under acceleration by heat at 37 and 50 °C temperatures. Physical and chemical evaluation had been carried out on 4th, 50th and 90th day, respectively. Chemical assay had been performed by UV light absorption spectroscopy. After 3 months stability data were analyzed by statistical regression analysis and plotted against time. It followed pseudo first order degradation kinetics. Rate constants were found out from this plot and set up in Arrhenious equation to find out the energy of activation. The rate constants were 14.1604 X 10-5 and 30.1 X 10-5 days-1 for 37 and 50 °C, respectively. According to Q10 method this value was used to determine the exact Q10 factor, which indicated its lower estimate value. Taking this lower value the expire dates were predicted for 5.3 yrs, 3.8 yrs, and 2.2 yrs, at 20 °C, 25 °C and 33 °C, respectively. These temperatures were the room temperatures of winter zone, Asian subcontinent and tropical zone, respectively. doi: 10.3329/taj.v18i2.3191 TAJ 2005; 18(2): 113-117